Re‐Regulation in the Post‐WTO Period? A Case Study of Vietnam's Food Retailing Sector. (18th March 2014) - Nguyen, Hai T. H.; Deverteuil, Geoff; Wrigley, Neil; Ruwanpura, Kanchana N.
Abstract Academic interest on domestic regulatory (and re‐regulatory) impacts of retail foreign direct investment remains surprisingly under‐researched, despite high‐profile campaigns, particularly in Southeast Asia, to rein in the expansion of retail transnational corporations. This paper focuses on the trends of re‐regulation of foreign retailers, particularly in the food sector, in Vietnam before and after the accession to the World Trade Organization (WTO) in 2007. The findings reveal a complex layering of regulation, some of it a holdover from the pre‐2007 period and some of it occurring since WTO accession, in the form of the controversial Economic Needs Test.